Response to ‘The association of clozapine and haematological malignancies needs to be replicated by other studies and more importantly by analyses of subsamples from VigiBase’ - Chrétien, Basile; Lelong‐Boulouard, Véronique; Alexandre, Joachim; Fédrizzi, Sophie; Dolladille, Charles (Psychological Medicine, 2020)
An abstract is not available for this content. As you have access to this content, full HTML content is provided on this page. A PDF of this content is also available in through the ‘Save PDF’ action button.